Realist studies of oppression, emancipation and resistance. (September 2018) - O'Mahoney, Joe; Vincent, Steve; Harley, Bill
This article introduces two papers in a special section of this journal. It explains why realist studies of oppression, emancipation and resistance are needed. We trace the development of studies in this area, noting their Marxist roots, divergence with post-structural theorising and more recent critical realist advancements. We conclude by highlighting the weaknesses in studies of this area and by arguing that progress is important for understanding how emancipation from oppression might be possible.